Decision sourcing : decision making for the agile social enterprise - Roberts, Dale, 1963- (Gower, 2013)
Decision Sourcing lays bare the poverty of decision making processes in today's corporate world and delivers insight into how social tools are providing new sources of information, how they are challenging hierarchy and how they are providing opportunities for growth and agility through aligned and inclusive decision making.